Peran Pemerintah dalam Perencanaan Pembangunan Lapangan Golf Kintamani dengan Prinsip Pariwisata Berkelanjutan - Rila Hilma (Bina Nusantara University, 2013)
Planning a tourist destination, some aspects need to be considered concerning government’s role, surrounding society, and sustainable development principles. The project of golf court in caldera Gunung Batur must be analysed by some experts. This study aims to anticipate some new troubles that might come up when the construction of golf court begins. Above it all, every study has opportunity to be applied whether by regional or national government, who responsibly takes control of the region, once they approved the project. Based on it, the plan of golf court construction in Kintamani, Bangli regency, Bali Province (as cited by www.bisnisbali.com on 27th January 2011) proposed by Ministre Jero Wacik and approved by the parlement members of DPRD Bangli, concerns the principles of sustainable tourism which could prevent, especially Kintamani region, from deconstructed side effects of the development. This research applies qualitative-descriptive method supported by literature review and news from media, especially online media which are able to provide the actual news from Kintamani region.